Characterization of Oral Squamous Cell Carcinoma Associated Inflammation: A Pilot Study - Laliberté, Catherine; Ng, Nicole; Eymael, Denise; Higgins, Kevin; Ali, Aiman; Kiss, Alex; Bradley, Grace; Magalhaes, Marco A. O. (Frontiers in Oral Health, 2021)
Background: Oral squamous cell carcinoma (OSCC) is a devastating disease that is usually associated with a dense associated inflammatory infiltrate. Characterizing tumor-associated inflammation is critical to understand the pathogenies of tumor development and progression. Methods: We have tested a protocol to analyze tissue and salivary immune cells and mediators of 37 patients with OSCC at different stages and compared to eight chronic periodontitis patients and 24 healthy controls. Tissue analysis was based on fluorescent immunohistochemistry (FIHC) and inflammatory mediators were analyzed using a Luminex-based 30-Plex panel. Immune cells were analyzed using multichannel flow cytometry including CD45, CD66b, CD3, CD4, CD8, CD25, CD56, CD68, CD138, PD-1, and PD-L1. Results: We show an increase in OSCC-associated inflammation characterized by increased pro-inflammatory cytokines including IL-6, IL-8, TNFα, and GMCSF and increased salivary immune cells. Conclusion: We described a new method to analyze salivary inflammatory markers that can be used in future studies to monitor disease progression and prognosis.